2013
DOI: 10.1080/19424280.2012.757810
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rearfoot and forefoot midsole hardness on biomechanical and perception variables during heel-toe running

Abstract: Purpose: Running shoe cushioning research has focused widely on rearfoot (RF) characteristics, whereas forefoot (FF) characteristics have been rather neglected. However, altered cushioning may affect running biomechanics and respective subjective perception at RF and FF. Thus, this research compared the effect of running shoes with different midsole hardnesses at RF and FF. Methods: Twenty-eight heel-toe runners were tested in five experimental shoe conditions that featured three segmented EVA midsoles (RF, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 29 publications
(34 reference statements)
7
43
1
1
Order By: Relevance
“…This means that subjective evaluation of running shoe features using VAS may not reflect one's overall shoe preference when two models are compared directly. The moderate agreement between the perception assessment procedures reinforces previous studies in the literature that testing subjective perception is complex and difficult (Hennig 2011;Kong and Bagdon 2010;Lam, Sterzing, and Cheung 2011;Miller et al 2000;Mills, Blanch, and Vicenzino 2010;Mündermann, Stefanyshyn, and Nigg, 2001;Mündermann et al 2002;Sterzing et al 2013). Furthermore, it raises some concerns regarding the common use of VAS in assessing subjective characteristics of footwear in a laboratory setting because the test results do not necessary reflect one's shoe preference in real life.…”
Section: Shoe Rankings Differed Between Assessment Methodssupporting
confidence: 78%
See 3 more Smart Citations
“…This means that subjective evaluation of running shoe features using VAS may not reflect one's overall shoe preference when two models are compared directly. The moderate agreement between the perception assessment procedures reinforces previous studies in the literature that testing subjective perception is complex and difficult (Hennig 2011;Kong and Bagdon 2010;Lam, Sterzing, and Cheung 2011;Miller et al 2000;Mills, Blanch, and Vicenzino 2010;Mündermann, Stefanyshyn, and Nigg, 2001;Mündermann et al 2002;Sterzing et al 2013). Furthermore, it raises some concerns regarding the common use of VAS in assessing subjective characteristics of footwear in a laboratory setting because the test results do not necessary reflect one's shoe preference in real life.…”
Section: Shoe Rankings Differed Between Assessment Methodssupporting
confidence: 78%
“…Previous research have shown that runners were able to perceive differences in rearfoot and forefoot hardness (Sterzing et al 2013) and that cushioning shoes with good shock attenuating properties were generally preferred (Hennig 2011;Kong and Bagdon 2010). When compared with the least favoured model (C), the top ranked model (D) is characterised by heavier mass (þ 27.0%), increased rearfoot (þ 13.3%) and forefoot (þ 31.3%) thickness, higher forefoot stiffness (þ 21.1%), lower forefoot impact (2 4.6%) and higher forefoot energy return (þ 11.2%) ( Table 3).…”
Section: Shoe Preference and Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers report increased positive peak axial tibial acceleration values in impact assemblies and maximum loading rate of the impact peak in running with increased hardness of footwear (DeWit et al, 1995;Sterzing et al, 2013).…”
Section: Introductionmentioning
confidence: 99%